Enumeration of Pathogenic Bacteria from Automatic Teller Machine (ATMs) Keyboard, a Case Study of ATM Machine of Branch 448 Unity Bank Plc Jahun, Jahun Local Government, Jigawa State (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
This study investigated the pathogenic bacteria from automatic teller machine (ATMs) keyboards, a case study of ATM machine of branch 448 Unity Bank PLC Jahun, Jahun Local Government, Jigawa state. ATM is used by hundreds of people in a day in the world (including Nigeria). The grab sampling techniques were used to obtain the sample. The cultural, Gram stained and biochemically tests were conducted. A total of 100 samples were collected from the ATM keyboard in the study area in April 2022, Staphylococcus aureus has the highest prevalence of 48%, E. coli 43% and P. aeruginosa has the lowest prevalence of 9% in this study. Pathogenic bacteria such as E. coli; P. aeruginosa and S. aureus on the ATMs were isolated. The research work revealed that there is a relationship between the Automatic Teller Machines (ATMs) and the isolated pathogenic bacteria. A bowl containing sanitiser should be provided by the bank management at every ATM location so that users can disinfect their hands after using the ATMs and also ATM Cleaners should be employed by the bank management so that they can disinfect the metallic buttons at intervals using compatible disinfectants.
Keywords: ATM keyboard; Pathogenic bacteria; Staphylococcus aureus; E. coli; P. aeruginosa